Grinding the Internal Strength: Training, Incentives, and Perceived Employability In Indonesia - Rahmawati, Andi; Sunrawali, Andi Nonong; Ishak, Andi Abdul Razak; Rahmat, Muhammad Rijal Alim (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
How the future employees shape their job filling is subject to their innate capacities. This study investigates the neglected conversation in perceived employability is predicted from the confidence of having sufficient training and knowledge, while incentive potentially moderates the intention to have sufficient training for better knowledge. This study employs PLS-SEM to construct path and bootstrap coefficients by sourcing the data from 160 unemployed trainees of pre-work recipients in Indonesia. This study found that all proposed hypotheses are accepted, and the moderating effect is similarly reinforced. Training is a strong predictor to perceived employability, second to knowledge only. Incentive can boost, despite minimum relevance, the confidence that training is essential for knowledge generation. This study implies the best use of self-funding to advance the internal capacities and capabilities for better job absorption.